Perancangan Aplikasi Diagnosa Tromboflebitis Dengan Algoritma Sequential Minimal Optimization - Siti Rohana Syahputri (Journal of Informatics, Electrical and Electronics Engineering, 2021)
Expert system (Expert System) is a branch of artificial intelligence (Artificial Intelligence) that seeks to adopt human knowledge into computers designed to model problem-solving abilities like an expert. Expert systems act like experts in their fields containing facts and heuristics to solve certain problems. Expert systems are based on knowledge systems, allowing computers to draw conclusions from a set of existing rules. Maintaining health is an obligation that is often forgotten by humans so that disease grows in the human body. Thrombophlebitis is inflammation or swelling of the veins (veins) caused by blood clots that occur in the veins. Inflammation generally occurs in veins in the legs, although it does not rule out the veins of the hands or neck. To find reliable information on the diagnosis of thrombophlebitis requires an expert who is proficient in the field of thrombophlebitis diagnosis, but due to the limited working hours of an expert, thrombophlebitis diagnosis becomes a problem that prevents sufferers from obtaining information on thrombophlebitis diagnoses quickly and accurately. To solve these problems. To diagnose thrombophlebitis, it can be done using the SMO algorithm. The process is carried out by SMO to speed up the training process in diagnosing thrombophlebitis.